Shift towards a low-carbon economy: An impact of support under operational programmes on climate and energy targets - Michał Ptak (Economic and Environmental Studies (E&ES), 2016)
The aim of the analysis is to estimate the impact of Cohesion Policy in the programming period 2014-2020 on the EU climate and energy targets in 9 chosen European countries and on transition into low-carbon economies. The paper discusses benefits expected at the beginning of the 2014-2020 programming period. The benefits include reduction of greenhouse gas emissions of at least 9 million tonnes CO2 equivalent per year, increase in the capacity of renewable energy sources and improvement in the primary energy consumption. The analysis of operational programs allowed also for a rough estimate of the amount of the support for different types of energy investments in EU Member States. The paper finds that the largest financial support for low carbon transformations will be provided under operational programmes in Poland.
Keywords: H23; Q54; 330; climate change; energy; greenhouse gases; subsidies; Cohesion Policy